Interior graphic standards - Binggeli, Corky (Wiley graphic standards, 2012)
"The student edition of Interior Graphic Standards, Second Edition, carefully selects content from the professional book that specifically pertains to students to cover critical information on interior architecture and design. Topics new to this edition include: residential design, exterior construction as it relates to interiors, sustainable materials, expanded coverage of equipment and furnishings, building information modeling (BIM), integrated project delivery (IPD), and virtual collaboration. A password-protected instructor web site includes pedagogical materials, suggested course schedules, essay exam questions, project requirements, lecture notes, presentations, and review questions" -- Provided by publisher.